Case Report: Lessons learned from large animal implantation of an all-natural tissue engineered vascular graft - Dumitru, Alexandru I.; Wonski, Bryan T.; Cole, Renée A.; Weaver, Mitchell R.; Carpenter, Kelsey C.; Kabbani, Loay S.; Lam, Mai T. (Frontiers in Transplantation, 2025)
Cardiovascular disease continues to be the number one cause of morbidity and mortality across the world. Coronary artery bypass graft (CABG) procedures are the most commonly performed major surgery in the U.S. Grafts are difficult to source as patients do not have many sites from which to harvest donor tissues as autografts. Plastic grafts have issues of infection and are only used as a last resort. Tissue engineered vascular grafts have potential to solve the need for all-natural vascular grafts in the clinic. In this study, we evaluate the feasibility of a completely biological engineered vascular graft for implantation in a large animal model of a rabbit. An all-biological tissue engineered graft was grown in our laboratory, composed of a tunica adventitia derived from human dermal fibroblasts and a tunica media made from human aortic smooth muscle cells. The all-biological engineered graft exhibited the “look and feel” of a natural vessel. The engineered graft was implanted into the abdominal aorta of a New Zealand rabbit. The graft easily anastomosed to the native abdominal aorta and showed no leakages. Once reperfused, the graft was able to withstand blood flow briefly, prior to exhibiting dissection between the media and adventitia. Color doppler ultrasound showed flow through the abdominal aorta, however, not through the graft region due to the dissected layers creating a blockage. These results support a shift from the traditional paradigm of designing vascular grafts to mimic the multi-layered native structure. The two-layer engineered graft tested here exhibited dissection between the layers, a phenomenon that has yet to be reported in the field to our knowledge. Based on these findings, we recommend a single layer engineered graft to best prevent dissection.